Studying co-tagging networks in learning object repositories - Zervas, P.; Alifragkis, C.; Sampson, Demetrios (2016)
© 2016 IEEE.Co-tagging refers to the process of adding the same tag to one or more digital resources by two or more taggers. This process can be modelled as a social network, also known as co-tagging network, where the actors are the taggers and the relationships between them are the common tags that they have used. Co-tagging networks have been studied by applying social network analysis (SNA) metrics so as to: (a) draw significant insights about the influence of central users to the (tagging) behaviour of other users and (b) identify clusters of taggers based on the content of the tags that they use. Nevertheless, there are no previous works, which have studied co-tagging networks in the field of Learning Object Repositories (LORs). In this paper we aim to address this issue by studying the co-tagging network of a specific LOR, namely the OpenScienceResources (OSR) Repository.